Humor dalam Iklan “Iritology” dari Sudut Pandang Generasi Z - Setiawan, Brandon; Sukendro, Gregorius Genep (Kiwari, 2026)
This study aims to understand how Generation Z interprets the style of comedy in the 'Iritology' advertising series. The background of the research stems from the phenomenon of changing humor preferences in the digital era, where Gen Z is growing up in a fast-paced, dynamic, and ever-changing internet culture. This study uses the theory of incongruity humor, the characteristics of Generation Z as digital natives, and the concept of digital pop culture as its theoretical foundation. The research method employed is a qualitative case study with in-depth interviews, documentation, and literature study techniques. Data analysis is conducted through stages of data reduction, data presentation, and conclusion drawing, combined with thematic analysis. The results indicate that the humor in the Iritology ad series is perceived as absurd, hyperbolic, and parodic. However, its relevance varies between early and late Generation Z. The humor of the scene is influenced by experience with popular culture, meme consumption, and the relatability of the informants. The emotional response that arises is light, spontaneous, and tends to be temporary. Overall, Iritology humor is considered entertaining, but it does not yet fully reflect the sense of humor of today's Generation Z in depth. Penelitian ini bertujuan untuk memahami bagaimana Generasi Z memaknai gaya komedi dalam seri iklan “Iritology”. Latar belakang penelitian berangkat dari fenomena perubahan preferensi humor di era digital, di mana Gen Z berkembang dalam budaya internet yang cepat, dinamis, dan terus berubah. Penelitian ini menggunakan teori humor inkongruensi, karakteristik Generasi Z sebagai ‘digital natives’, serta konsep budaya populer digital sebagai landasan teoritis. Metode penelitian yang digunakan adalah studi kasus kualitatif dengan teknik wawancara mendalam, dokumentasi, dan studi pustaka. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan yang dipadukan dengan analisis tematik. Hasil penelitian menunjukkan bahwa humor dalam seri iklan Iritology dipahami sebagai humor absurd, hiperbola, dan parodi, namun tingkat relevansinya berbeda antara Generasi Z awal dan Generasi Z akhir. Kelucuan adegan dipengaruhi oleh pengalaman budaya populer, konsumsi meme, serta tingkat relatabilitas informan. Respons emosional yang muncul bersifat ringan, spontan, dan cenderung sementara. Secara keseluruhan, humor Iritology dinilai menghibur, namun belum sepenuhnya mencerminkan selera humor Generasi Z masa kini secara mendalam.